The role of postoperative radiotherapy in prostate cancer patients - Zarzycka, Małgorzata; Ziółkowska, Ewa; Wiśniewski, Tomasz; Windorbska, Wiesława; Żyromska, Agnieszka; Wolski, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The aim of the study was to evaluate the effectiveness of postoperative radiotherapy in prostate cancer patients with unfavorable prognostic factors. Material and methods: In the years 2002–2008, 121 consecutive prostate cancer patients underwent radical prostatectomy and postoperative radiotherapy. The median dose was 64 Gy (range: 60–72 Gy). Biochemical and clinical progression-free survival were estimated. Univariate and multivariate analyses were used to analyze clinicopathological variables associated with treatment failure. Results: The median follow-up was 27 months. Three-year bPFS was 72%. On univariate analysis it was influenced by: extracapsular tumor extension (60% vs. 75%, p = 0.0232), seminal vesicles invasion (52% vs. 85%, p = 0.00041), Gleason score  7 (65% vs. 86%, p = 0.044) and the use of hormonal therapy (50% vs. 80%, p = 0.0058). On multivariate analysis bPFS was associated with: TNM stage (HR = 3.19), postoperative hormonal therapy (HR = 2.6), total irradiation dose (HR = 0.82) and the maximum pretreatment level of prostate-specific antigen (PSA) (HR = 0.95). Three-year cPFS was 84%. On univariate analysis it was influenced by: preoperative PSA level > 10 ng/ml (75% vs. 90%, p = 0.04), vascular-nerve bundles involvement (63% vs. 88%, p = 0.0031), adjacent organs infiltration (50% vs. 85%, p = 0.018) and the use of postoperative hormonal therapy (62% vs. 90%, p = 0.02). On multivariate analysis cPFS was associated with: TNM stage (HR = 2.68), postoperative hormonal therapy (HR = 3.61) and total irradiation dose (HR = 0.78). Conclusions: Postoperative radiotherapy in patients with unfavorable prognostic factors provides good biochemical and local control. Total irradiation dose and postoperative hormonal therapy are important treatment factors influencing prognosis.